Associations between binge drinking and obesity-related anthropometric measures: Results from the national health and nutrition examination survey. (December 2022) - Wynne, Jaison; Wilson, Patrick
Abstract: Aims: Limited population-level data are available on the links between binge drinking and different measures (traditional and novel) of obesity in America. This study evaluated the associations between binge drinking and obesity anthropometric measures in adult Americans. Methods: This was a cross-sectional, observational study of 4098 adults from the 2013–2016 National Health and Nutrition Examination Survey. Body mass index, waist circumference (WC), and trunk-to-leg-volume ratio were assessed, along with binge drinking. Logistic regression was used to examine associations between binge drinking and obesity measures, by gender and age sub-groups. Results: Men engaged in more binge drinking than women. For men and women aged 20–39 yr, those who binge drank 1–12 times yearly had approximately 25–40% lower odds of obesity than abstainers when using WC and trunk-to-leg-volume ratio, though the association was only significant for WC. Middle-aged men (40–59 yr) reporting >12 yearly binges had higher odds (2.30, 95% CI: 1.19–4.46) of elevated trunk-to-leg-volume ratio than abstainers. Associations between monthly binging and obesity measures were non-significant. Conclusions: Associations between obesity and binge drinking depend on age, gender, and the method of quantifying obesity. Research and public health efforts related to binge drinking and obesity should consider the complexity of these associations. Highlights: Adults 20–39 years old who binged 1–12 times yearly had about 40% less odds of elevated waist circumference than abstainers. Middle-aged men with >12 yearly binges had more than double the odds of elevated trunk-to-leg-volume ratio than abstainers. Associations between binge drinking and obesity are conflicting and depend on age, gender, and method of assessing obesity.